Diagnostic Dilemmas: Overlapping Features of Brugada Syndrome and Arrhythmogenic Right Ventricular Cardiomyopathy - Hoogendijk, Mark (Frontiers in Physiology, 2012)
Arrhythmogenic right ventricular cardiomyopathy (ARVC) and Brugada syndrome are distinct clinical entities which diagnostic criteria exclude their coexistence in individual patients. ARVC is a myocardial disorder characterized by fibro-fatty replacement of the myocardium and ventricular arrhythmias. In contrast, the Brugada syndrome has long been considered a functional cardiac disorder: no gross structural abnormalities can be identified in the majority of patients and its electrocardiographic hallmark of coved-type ST-segment elevation in right precordial leads is dynamic. Nonetheless, a remarkable overlap in clinical features has been demonstrated between these conditions. This review focuses on this overlap and discusses its potential causes and consequences.